STUDI BIBLIOMETRIK SDG 3: PEMETAAN RISET GLOBAL TENTANG KESEHATAN DAN KESEJAHTERAAN SUMBER DAYA MANUSIA - Aulia Fadwi (LPPM Universitas Negeri Surabaya, 2026)
This study aims to map the global research landscape on human resource health and well-being using a bibliometric approach supported by Biblioshiny, Bibliometrix, and VOSviewer. By analyzing Scopus-indexed publications from 1996 to 2025, this research identifies long-term trends, dominant subject areas, research achievements, challenges, and future opportunities in the field. The findings reveal a significant increase in publications, particularly after 2019, driven by rising awareness of mental health, workplace well-being, and the global impact of the COVID-19 pandemic. Visualization through VOSviewer demonstrates that the knowledge structure surrounding human resource well-being is multidisciplinary, involving public health, psychology, management, clinical medicine, and policy studies. The keyword co-occurrence network also highlights that research in this domain is human-centered and closely aligned with Sustainable Development Goal 3 (Good Health and Well-being). Despite substantial progress, research gaps remain, especially in cross-cultural studies, system-based health workforce models, and holistic well-being frameworks. This study concludes that future research should focus on strengthening global collaboration, integrating psychological and organizational perspectives, and developing evidence-based interventions to improve workforce health and human capital development worldwide.